Pijat Bayi Dengan Pertumbuhan Dan Perkembangan Pada Bayi Usia 0-12 Bulan - panglipurwati, Cicik; Hamim, Nur (MIDWIFERY JOURNAL, 2023)
Background: Baby massage is an expression of affection between parents and children through touching the skin. Meanwhile, development is the increasing perfection of abilities, skills and more complex body functions in gross motor skills. The prevalence of child development problems in various developed and developing countries, including America, is 12-16%, Argentina 22% and Hong Kong 23%. According to the Indonesian Ministry of Health (2013), 16% of babies in Indonesia experience neurological and brain development disorders ranging from mild to severe. One form of growth and development stimulation that has been carried out is baby massage (Kepmenkes RI, 2020). Massage is one of the oldest treatment methods in the world. Objective: The aim of this research is to determine the relationship between baby massage and growth and development in babies aged 0-12 months in the working area of the Sumberjambe Jember Community Health Center. Method: The population in this study were mothers with children under five 0 - 12 months with a total of 146 with a sample of 107 respondents taken using simple random sampling techniques and Chi-Square Tests data analysis. The results of the study of 107 samples showed that 86 respondents had increased or good weight. (80.4%) after the massage, while the weight category did not increase, 21 respondents (19.6%) obtained the weight category. Then a statistical test was carried out to obtain a p value of 0.00 because the p value <0.05. Meanwhile, the result is p = 0.02, which means there is a relationship between baby massage and growth and development in toddlers aged 0-12 months in the working area of the Sumberjambe Community Health Center, Jember. Conclusion: Babies received massage (80.4%), and weight rose 7.75%. There is a relationship between baby massage and growth and development in the working area of Sumberjambe Community Health Center, JemberSuggestion: Midwifery and health workers should continue to improve their understanding and skills in providing baby massage services in order to achieve growth and development in their babies.  Keywords ; Massage for Babies, Toddlers, Toddler Growth and Development ABSTRAK Latar belakang:Pijat bayi merupakan pengungkapan rasa kasih sayang antara orang tua dengan anak lewat sentuhan pada kulit.sedangkan perkembangan adalah bertambah sempurnanya kemampuan, keterampilan, dan fungsi tubuh yang lebih kompleks dalam kemampuan motorik kasar. Prevalensi masalah perkembangan anak diberbagai negara maju dan berkembang di antaranya Amerika sebesar 12-16%, Argentina 22% dan Hongkong 23%. Menurut Depkes RI (2013) menyatakan bahwa 16% bayi di Indonesia mengalami gangguan perkembangan saraf dan otak mulai ringan sampai berat Salah satu bentuk stimulasi tumbuh kembang yang selama ini dilakukan yaitu pijat bayi (Kepmenkes RI, 2020). Pijat merupakan salah satu metode pengobatan tertua di dunia.Tujuan: tujuan penelitian ini untuk mengetahui Hubungan pijat bayi dengan pertumbuhan dan perkembangan pada bayi usia 0-12 bulan di wilayah kerja puskesmas sumberjambe jember. Metode:Populasi pada penelitian ini adalah ibu dengan anak balita 0 – 12 bulan dengan jumlah 146 dengan sampel 107 responden yang diambil dengan teknik sampling simple random sampling dan analisa data Chi-Square Test.Hasil penelitian sebanyak 107 sampel didapatakan berat badan meningkat atau baik 86 responden (80,4%) setelah dilakukan pemijatan, sedangkan katagori berat badan tidak meningkat di dapatkan sebanyak 21 responden (19,6%), Kemudian dilakukan uji statistik  diperoleh nilai p value sebesar 0.00  karena p value < 0.05. Sedangkan hasil dari p = 0,02 yang berarti ada hubungan pijat bayi dengan pertumbuhan dan perkembangan padabalita usia 0-12 bulan diwilayah kerja puskesmas sumberjambe, jember.Kesimpulan:Bayi melakukan pemijatan ada (80,4%), dan BB naik 7,75% .ada hubungan pemijatan bayi dengan pertumbuhan dan perkembangan di Wilayah kerja puskesmas Sumberjambe, jemberSaran: Tenaga kebidanan dan kesehatan sebaiknya terus meningkatkan pemahaman dan keterampilan dalam memberikan layanan pijat bayi agar mencapai pertumbuhan dan perkembangan pada bayinya. Kata kunci ; Pijat Bayi, Balita, Tumbuh-kembang balita